SOME POINTS ON CASIMIR FORCES (Journal of Sciences, Islamic Republic of Iran)
Casimir forces of massive ferrnionic Dirac fields are calculated for parallel plates geometry in spatial space with dimension d and imposing bag model boundary conditions. It is shown that in the range of ma>>l where m is mass of fields quanta and a is the separation distance of the plates, it is equal to massive bosonic fields Casimir force for each degree of freedom. We argue this equality exists for any massive anyonic field in two-dimensional spatial space. Also the ratio of massless ferrnionic field Casimir force to its bosonic correspondent in d-dimensional spatial spaceis (1- )